2023
DOI: 10.1111/eth.13391
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive vocalizations during intergroup interactions in roost defense in the Spix's disk‐winged bat

Abstract: Animals engage in agonistic interactions to gain exclusive access to territories and resources. Understanding these interactions in bats, however, has proven difficult given their high mobility and nocturnal habits. For bats, roosts are a critical resource; thus, the study of agonistic behaviors associated with the use of these resources could provide valuable information to understand how and whether individuals monopolize them. Here, we used Thyroptera tricolor to study agonistic behaviors associated with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
2
2
Order By: Relevance
“…Therefore, the production of "screech" calls in this species, while strongly associated with foraging activities, is not considered to be exclusively associated with a feeding context (Clay et al, 2012). In contrast, the evidence collected in our study, together with results of previous studies (Chaverri et al, 2018(Chaverri et al, , 2021Chaverri & Gillam, 2016;Chaves-Ramírez et al, 2023;Montero & Gillam, 2015), shows that food-associated calls in T. tricolor are emitted exclusively in a feeding context, and that calls prompt social recruitment. Future studies are needed to confirm that T.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Therefore, the production of "screech" calls in this species, while strongly associated with foraging activities, is not considered to be exclusively associated with a feeding context (Clay et al, 2012). In contrast, the evidence collected in our study, together with results of previous studies (Chaverri et al, 2018(Chaverri et al, , 2021Chaverri & Gillam, 2016;Chaves-Ramírez et al, 2023;Montero & Gillam, 2015), shows that food-associated calls in T. tricolor are emitted exclusively in a feeding context, and that calls prompt social recruitment. Future studies are needed to confirm that T.…”
Section: Discussioncontrasting
confidence: 84%
“…Our recordings of feeding bats show that many individuals emitted distinct vocalizations while consuming an abundant prey item. This type of call has not been previously described in disc-winged bats (Chaverri et al, 2018, 2021; Chaverri & Gillam, 2016; Montero & Gillam, 2015), and is markedly different from calls emitted by this species in situations of distress (Chaves-Ramírez et al, 2023). We also observed that vocalizations prompted two responses in receivers which are typically associated with food-calling (Clay et al, 2012), namely increasing feeding-related behaviors and social recruitment.…”
Section: Discussioncontrasting
confidence: 62%
“…When searching for roosts, individuals probably target those areas, which would reduce the probability of flying bats accidentally joining other groups and roosting bats responding to non-groupmates. The events would be costly because individuals entering a roost occupied by another group face the risk of aggression [45].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, contact calling rates may not be explained by the individual identity of the receivers. In some taxa, call rates are influenced by the risk of becoming separated from one's group [41,42]; thus, contact calls may be produced for the entire group, not targeted at a single receiver, to remain in close contact with group members [43,44] or to avoid inter-group interactions, which could result in aggression [45]. In that case, we expect the best predictor of calling rate to be the caller, rather than the receiver or its kinship or association with the caller.…”
Section: Introductionmentioning
confidence: 99%